Clinical phenotypes of IgG4-related disease: an analysis of two international cross-sectional cohorts - Wallace, Z; Zhang, Y; Perugino, C; Naden, R; Choi, H; Stone, J; Harnden, A (BMJ Publishing Group, 2019)
OBJECTIVE:IgG4-related disease (IgG4-RD) is a heterogeneous, multiorgan condition of unclear aetiology that can cause organ failure. Difficulty recognising IgG4-RD contributes to diagnostic delays. We sought to identify key IgG4-RD phenotypes. METHODS:We used two cross-sectional studies assembled by an international, multispecialty network of IgG4-RD specialists who submitted 765 cases to derive and replicate phenotypic groups. Phenotype groups of disease manifestations and key covariate distributions across the identified groups were measured using latent class analysis. RESULTS:In the derivation cohort (n=493), we identified four groups with distinct manifestations: Group 1 (31%), Pancreato-Hepato-Biliary disease; Group 2 (24%), Retroperitoneal Fibrosis and/or Aortitis; Group 3 (24%), Head and Neck-Limited disease and Group 4 (22%), classic Mikulicz syndrome with systemic involvement. We replicated the identification of four phenotype groups in the replication cohort. Compared with cases in Groups 1, 2 and 4, respectively, cases in Group 3 were more likely to be female (OR 11.60 (95% CI 5.39 to 24.98), 10.35 (95% CI 4.63 to 23.15) and 9.24 (95% CI 3.53 to 24.20)) and Asian (OR 6.68 (95% CI 2.82 to 15.79), 7.43 (95% CI 2.97 to 18.56) and 6.27 (95% CI 2.27 to 17.29)). Cases in Group 4 had a higher median serum IgG4 concentration (1170 mg/dL) compared with groups 1-3 (316, 178 and 445 mg/dL, respectively, p<0.001). CONCLUSION:We identified four distinctive IgG4-RD phenotypes according to organ involvement. Being Asian or female may predispose individuals to head and neck-limited disease. These phenotypes serve as a framework for identifying IgG4-RD and studying its aetiology and optimal treatment.